Nghiên cứu khả năng sóng thần ven biển và hải đảo Việt Nam - Thủy, Nguyễn Ngọc (Vietnam Journal of Earth Sciences, 2004)
The possibility of Tsunami’s appearance along the coastal zone and islands of Vietnam